The Effect of Technology Absorptive Capacity and Digital Adoption on Business Performance of Msmes in Bali Province Through Business Innovation as A Mediating Variable - Tangkas Gede Hary Angga Purnama Damai; Dodie Tricahyono (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Digital transformation has emerged as a critical determinant for the sustainability of Micro, Small, and Medium Enterprises (MSMEs), particularly within tourism-centric economies such as Bali Province. This study aims to empirically analyze the influence of Technology Absorptive Capacity and Digital Adoption on MSME Business Performance, incorporating Business Innovation as a mediating variable. Employing a quantitative approach, primary data were collected from 400 MSMEs in Bali selected via simple random sampling. The data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings reveal that both Technology Absorptive Capacity and Digital Adoption exert a positive and significant effect on Business Performance, both directly and indirectly through Business Innovation. Notably, Digital Adoption demonstrated the strongest direct impact on performance, while Business Innovation was confirmed as a partial mediator that enhances the effect of technological capabilities on business outcomes. This study concludes that enhancing MSME performance requires not only the adoption of digital tools but also the organizational capacity to absorb technology for creating adaptive product and business model innovations.